2005
DOI: 10.1590/s0103-64402005000200006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave treatments on dimensional accuracy of maxillary acrylic resin denture base

Abstract: Microwave energy has been used as an alternative method for disinfection and sterilization of dental prostheses. This study evaluated the influence of microwave treatment on dimensional accuracy along the posterior palatal border of maxillary acrylic resin denture bases processed by water-bath curing. Thirty maxillary acrylic bases (3-mm-thick) were made on cast models with Clássico acrylic resin using routine technique. After polymerization and cooling, the sets were deflasked and the bases were stored in wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 13 publications
2
47
0
1
Order By: Relevance
“…Because acrylic resin dentures are considered semi-critical articles, they should undergo high-level disinfection or sterilization (8). The results of this study showed that the peracetic acid-based disinfectant promoted not only disinfection but also sterilization of the acrylic resin specimens because it completely eliminated both test sporulated microorganisms (Bacillus subtilis and Bacillus stearothermophilus).…”
Section: Discussionmentioning
confidence: 80%
“…Because acrylic resin dentures are considered semi-critical articles, they should undergo high-level disinfection or sterilization (8). The results of this study showed that the peracetic acid-based disinfectant promoted not only disinfection but also sterilization of the acrylic resin specimens because it completely eliminated both test sporulated microorganisms (Bacillus subtilis and Bacillus stearothermophilus).…”
Section: Discussionmentioning
confidence: 80%
“…Disinfection procedures should not cause dimensional changes or distortion of the acrylic resin denture base, otherwise the stability, retention and durability of the complete dentures can be compromised (8).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment in microwave oven at 604 W for 10 min produced the greatest discrepancies in the adaptation of maxillary acrylic resin denture bases to the stone casts [19]. Disinfection by microwave energy improved denture base adaptation when the traditional flask closure method was used, but did not alter the base adaptation in the restrictive flask closure method [20].…”
Section: Introductionmentioning
confidence: 95%